Impact of epizootics on mussel farms: Insights into microbiota composition of Mytilus species - Ben Cheikh, Yosra; Massol, François; Giusti-Petrucciani, Nathalie; Travers, Marie-Agnès (Microbiological research, 2024)
Outbreaks of marine mussel mortality on French farms could have different aetiologies. One of them implies Vibrio splendidus strains. Beyond the involvement of this pathogen, there is considerable evidence that diseases often result from interactions between several microbes and the host. In this study, we explored the bacterial communities associated with mussel species and the surrounding water collected from a mussel farm affected by mortalities. The microbiota of Mytilus edulis, Mytilus galloprovincialis and their hybrids displayed an abnormal abundance of Proteobacteria, in particular the genera Vibrio, Cobetia and Arcobacter. Despite the dysbiosis, the Mediterranean mussel showed a different microbiota profile with a higher richness and presence of the phylum Bacteroidetes. Bipartite network analyses at the level of bacteria families confirmed this finding and showed that the microbiomes of M. edulis and the hybrids tended to cluster together. In addition, injection of mussels with the virulent V. splendidus induced less mortality rate in M. galloprovincialis compared to the other Mytilus sp. suggesting a better resistance of the Mediterranean mussel to infection. Our findings point to a probable aetiology of pathobiome-mediated disease in mussels. To fully understand this phenomenon, more knowledge is needed on the roles of pathobiotic systems and their development during disease establishment.